MEDIATING ROLE OF PERCEIVED STRESS AMONG TEACHERS WORKING IN HIGHER EDUCATIONAL INSTITUTIONS (HEIS) WITH REFERENCE TO ICT INTEGRATION (CAHIERS MAGELLANES-NS, 2024)
The rapid advancement of ICT has significantly impacted educational settings, necessitating teachers to adapt to new teaching methodologies and tools. While ICT offers numerous benefits in enhancing teaching and learning experiences, it also introduces challenges and stressors for educators. The article aims to investigate the relationship between ICT integration and perceived stress levels among teachers, with a specific focus on how perceived stress mediates this relationship. ICT promotes worldwide connectedness, allowing academics to participate in international collaborations, exchange scholarly knowledge, and engage in multidisciplinary research projects. Furthermore, digital platforms have optimized operational efficiency inside institutions by simplifying administrative chores such as record-keeping, scheduling, and communication. The coping mechanisms employed by teachers to manage stress related to ICT integration have significant implications for both educational practice and policy. Effective stress management can lead to more successful and sustainable ICT implementation, enhancing teaching quality and student learning experiences. When teachers are equipped with robust coping strategies, they are more likely to embrace technological innovations and integrate them creatively into their curricula. This can foster a more dynamic and engaging learning environment that prepares students for a technologically advanced society. Based on the findings, propose recommendations for educational policymakers and institutional leaders to enhance ICT integration practices while minimizing stressors among teachers. These recommendations may include professional development programs, technological infrastructure improvements, and organizational support initiatives. The implications of effectively managing ICT-related stress extend beyond individual teachers, contributing to the overall improvement of the educational system and the achievement of broader educational goals.